La politica commerciale dell'unione europea nell'era della globalizzazione tra competitività internazionale e principi di concorrenza, coesione, partecipazione interna e sussidiarietà - Zedda, Laura (Polityka handlowa unii europejskiej w erze globalizacji pomiędzy konkurencyjnością międzynarodową a zasadami konkurencji, zbieżności, udziału wewnętrznego i subsydiarności, 2010)
The EC trade policy has always been basic for the world trade and the common European market. The most important legal aspects are connected with the relations between the EC and GATT and later WTO and EU, as well as with some relevant association agreements and trade agreements. The EU trade policy has taken place in European regional and multilateral system of the GATT, in accordance with the principles of internal competition and the international competitiveness. The EU has developed the link between trade policy and domestic economic cohesion, with the participation of local communities, based on the principle of subsidiarity. This principle and those of solidarity and sustainable development are considered essential for all external actions of the EU in the Treaty of Lisbon
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of W434rocław University of Economics; 2010; Nr 150, s. 425-434
Keywords: common commercial policy; EC-GATT; EU-WTO; regional European policy and global trade